PSYCHOLOGICAL FOUNDATIONS OF THE EDUCATIONAL PROCESS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This scientific article discusses the psychological features of the educational process. Communicative competence and the psychological approach of the teacher in his work, it also highlights the creative activities in small groups and their development factors.